Correcting common misconceptions to inspire conservation action in urban environments. Issue 2 (24th October 2018) - Soanes, Kylie; Sievers, Michael; Chee, Yung En; Williams, Nicholas S. G.; Bhardwaj, Manisha; Marshall, Adrian J.; Parris, Kirsten M.
Abstract: Despite repeated calls to action, proposals for urban conservation are often met with surprise or scepticism. There remains a pervasive narrative in policy, practice, and the public psyche that urban environments, although useful for engaging people with nature or providing ecosystem services, are of little conservation value. We argue that the tendency to overlook the conservation value of urban environments stems from misconceptions about the ability of native species to persist within cities and towns and that this, in turn, hinders effective conservation action. However, recent scientific evidence shows that these assumptions do not always hold. Although it is generally true that increasing the size, quality, and connectivity of habitat patches will improve the probability that a species can persist, the inverse is not that small, degraded, or fragmented habitats found in urban environments are worthless. In light of these findings we propose updated messages that guide and inspire researchers, practitioners, and decision makers to undertake conservation action in urban environments: consider small spaces, recognize unconventional habitats, test creative solutions, and use science to minimize the impacts of future urban development. Abstract : Article impact statement : Conserving native biodiversity is both important and achievable in urban environments.